Managing The Invisible Product: A Strategic Framework for Geospatial Infrastructure Investment in Indonesian Ride-Hailing Platform - Muhammad Iqnaul Haq; Aldianto, Leo (Journal Integration of Management Studies, 2026)
Geospatial capabilities have become critical dependencies in ride-hailing platforms, providing maps, routing, and location services. However, these foundational technologies frequently face prioritization challenges against more visible product features. This research addresses the "Invisible Product Paradox" by developing a Geospatial Product Strategy Framework for Indonesian ride-hailing platforms, using PT GoTo Gojek Tokopedia Tbk as the primary case. Employing a sequential mixed-methods design, the study integrates qualitative analysis of eight expert interviews (275 coded quotations using Atlas.ti) with quantitative validation through sentiment analysis of 4,806 user reviews. The theoretical lens combines Jobs-to-be-Done, Product-Market Fit, and Platform Strategy theories. Two complementary analyses were conducted: an independent platform-based validation (Kimola.com) identified a -1.07 star penalty across 586 geospatial reviews (12.19%), while the primary keyword-filtered analysis revealed a -1.21 star penalty across 520 reviews (10.81%, p<0.001). Three emergent concepts were identified: the Invisible Product Paradox, Silent Killer Effect, and Frequency-Severity Disconnect. The framework resulting from this research comprises three integrated tools: Job-to-Geo Impact Matrix, PMF Threshold Metrics Framework, and Build-vs-Buy Geospatial Sourcing Decision Framework, providing systematic approaches for geospatial investment prioritization in emerging market contexts.